Tradisi Pernikahan Suku Banjar Maantar Jujuran Ditinjau melalui Nilai Dasar Insani - Mauliddina, Sintya; Yuwanto, Listyo (VISA: Journal of Vision and Ideas, 2024)
One of the traditions in Indonesia related to marriage is the honest mantar of the Banjar tribe. The tradition occurs after the proposal takes place and before the wedding ceremony, because in the honest maantar tradition the man delivers symbolic gifts and a mutually agreed amount of money. The aim of this research is to conduct a literature study regarding wedding traditions in the Banjar tribe. We try to relate this tradition of psychological values to the theory of basic human values. The method used is qualitative literature study with data collection techniques using sources from relevant journals and books. The results obtained in the honesty maantar tradition have psychological meaning and values, of the 10 small values described, 5 of them are included in this tradition, namely strength, conformity, self-achievement, security and stimulation. There are 3 of the 4 big values, namely conservation, openness to change and self-improvement.